The not so terrible two's - Learning Seed Company; Stage Fright Productions ([Lake Zurich, Ill.] : Learning Seed, 2005)
This video watch the two-year olds children as they demonstrate the milestone of one of child development's most confusing and exiting years
Writer & executive, Christine Shrank
Narrator : Marty Peterson
Keywords: Toddlers -- Development; Child development; Toilet training